Identification of cation elements in PM10 concentration in industrial area of Penang - Ab Kadir, Zairah; Yusoff, Mahani; Awang, Norrimi Rosaida; Jani, Musfiroh; Arieff, Muhammad; Selvam, Bawani; Sulaiman, Muhammad Azwadi; Abdus Salam, Mohammed (Universiti Malaysia Kelantan, 2017)
This study aims to investigate the concentrations of particulate matter with aerodynamic diameter less than 10 micron (PM10) and their associated cation elements in PM10. The sample of PM10 were collected at Royal Malaysian Customs Department (N5° 22’ 012”; E100° 23’589”) located in Perai Industrial Area, Penang, from June to September 2015. The sampling was carried out during the southwest monsoon and a total of 12 samples were collected using low volume sampler (LVS). Result suggested that there are five elements that commonly identified from PM sampled which are ammonium, sodium, potassium, calcium and magnesium. The concentrations of the cation from all four months in the industrial area shows the order of NH4 + > Ca+ > K+ > Mg2+ > Na+ . The lowest nand highest concentrations calculated both were ammonium (0.012 µg/m³) in July and (0.873 µg/m³) September, respectively.